REINFORCEMENT OF DEVELOPING HIGHER ORDER THINKING SKILLS BASED LEARNING TOOLS IN MADRASAH KOTA JAMBI - Suryani, Hilma; Hidayati, Hidayati; Rozal, Edi; Andriani, Reni; Tartila, Tartila (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The current community service aims at training and mentoring the elementary school teachers to develop higher order thinking skills based learning tools. Higher order thinking skills have become the vital part that must be included in teaching and learning activities. It enables the students to be able to compete globally. The program involved twenty four teachers at Madrasah Nurul Yaqin Kota Jambi. The method of community service was service learning. The school was selected as the site of community service by considering the active participation of the school in attending any workshops held by different institutes. The results indicated that the participants were satisfied with the training since they could figure out the how to develop higher order thinking skills based learning tools. Also they could implement the developed learning tools in their own classrooms.